Antifungal Activity of Actinomycetes from Vermicompost and Their Morphological and Biochemical Characterization - Baniya, Rishi; Vaidya, Gita S (Nepal Journal of Science and Technology, 2012)
Thirty eight actinomycetes were isolated from saw dust and husk containing vermicompost samples. Of them, four (10.5%) were active against at least one of the tested phytopathogenic fungi; Fusarium oxysporum, F.moniliforme, F. proliferatum, Stemphylium botryosum, Exserohilum turcicum and human pathogenic fungi; Candida albicans and Aspergillus spp. during dual culture method. Of them, VAH3 showed broad spectrum activity against both pathogenic fungi with maximum inhibition of 24.53 ± 0.20% against F. oxysporum and minimum inhibition of 12.37 ± 0.24% against Stemphylium botryosum on solid agar surface. In agar well diffusion method, only VAH3 showed broad spectrum activity with maximum inhibition diameter of 14 mm against F. proliferatum and minimum inhibition diameter of six mm against Sclerotium rolfsii. Among them, one promising strain Streptomyces VAH3 was selected for further study. The minimum inhibitory concentrations of crude antifungal agent against F. oxysporum, Stemphylium botryosum, and Exserohilum turcicum, Candida albicans and Aspergillus spp. were found to be 560 ?g/ml, 1120 ?g/ml, 1120 ?g/ml, 560 ?g/ml and 1120 ?g/ml, respectively. Morphological, biochemical and physiological tests confirmed that all four potent strains were from Streptomyces genus. DOI: http://dx.doi.org/10.3126/njst.v12i0.6486 Nepal Journal of Science and Technology 12 (2011) 97-102